1981
DOI: 10.1523/jneurosci.01-03-00318.1981
|View full text |Cite
|
Sign up to set email alerts
|

Local circuit synaptic interactions in hippocampal brain slices

Abstract: The hypothesis that recurrent inhibition in the hippocampus is mediated by interneurons was tested with simultaneous intracellular recordings from the CA1 region of guinea pig hippocampal slices in vitro. In recordings from 101 pairs of pyramidal cells, no interactions were detected in 87% of the pairs. In 13% of the pyramidal cell pairs, spike trains induced in one cell caused inhibitor postsynaptic potentials (IPSPs) in the second cell. No excitatory interactions were detected. In recordings from 43 pairs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
2
2

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(130 citation statements)
references
References 21 publications
6
120
2
2
Order By: Relevance
“…Firstly, local neuronal circuitry can be studied more directly than was previously possible (MacVicar andDudek 1980, Knowles andSchwartzkroin 1981) by the combination of electrophysiology, staining of neurones with fluorescent dyes and image analysis. Pairs of neurones can be filled with fluorescent dyes during simultaneous whole-cell recording.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, local neuronal circuitry can be studied more directly than was previously possible (MacVicar andDudek 1980, Knowles andSchwartzkroin 1981) by the combination of electrophysiology, staining of neurones with fluorescent dyes and image analysis. Pairs of neurones can be filled with fluorescent dyes during simultaneous whole-cell recording.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on how a slice is cut, the 500-600 ìm intergroup separation may be either about right, or too small, for the CA1 pyramidal cell axon spread. On the other hand, CA1 pyramidal cell collaterals are expected to innervate cells in target fields with lower probability than do basket cells (Knowles & Schwartzkroin, 1981;Sik et al 1995), so that the effect of longer-range CA1 pyramidal axons may not be critical. Of course, basket cells and pyramidal cells do not exist in a 1:1 ratio in the hippocampus, interneurones of all types constituting a minority of the cells.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…With tetanic stimulation at two or more sites, oscillations in CA1 can become tightly synchronized (< 1 ms mean phase lag) at distances of at least 4·5 mm (Traub, Whittington, Stanford & Jefferys, 1996b; I. M. Stanford & J. G. R. Jefferys, unpublished data), so that an important feature of the in vivo phenomenon is captured in vitro. The relative sparseness of pyramidal cell-pyramidal cell synaptic connections in CA1 in vitro (Knowles & Schwartzkroin, 1981;Christian & Dudek, 1988;Thomson & Radpour, 1991) renders the analysis of the circuitry simpler than is the case in the neocortex. Electrophysiological data from the CA1 region in vitro, along with network simulations of compartmental neurones, suggest that synaptically interconnected networks of interneurones alone can generate ã oscillations, but that the properties of the oscillation are modified, in important ways, by the participation of pyramidal cells.…”
mentioning
confidence: 99%
“…The first studies of morphologically identified interneurons reported that interneurons were characterized by brief-duration action potentials, and therefore have been referred to as "fast-spiking" cells (Schwartzkroin and Mathers, 1978;Knowles and Schwartzkroin, 1981;McCormick et al, 1985). In addition, interneurons are characterized by a large afterhyperpolarization following action potentials, weak spike frequency adaptation, and short time constants (Schwartzkroin and Mathers, 1978;McCormick et al, 1985;Lacaille et al, 1987;Lacaille and Schwartzkroin, 1988;Lacaille and Williams, 1990;Scharfman, 1992b).…”
Section: Intrinsic Properties and Patterns Of Dischargementioning
confidence: 99%
“…Pyramidal-shaped cells were also distinct in that they often adapted. Many hippocampal interneurons do not appear to adapt (Schwartzkroin and Mathers, 1978;Knowles and Schwartzkroin, 1981) although there arc exceptions (Kawaguchi and Hama, 1990;Lacaille and Williams, 1990;Buhl et al, 1994b;Han, 1994). It is difficult to make a rigorous comparison of adaptation among different types of interneurons because previous studies have not necessarily quantified adaptation nor have they examined it in similar ways.…”
Section: Intrinsic Properties and Patterns Of Dischargementioning
confidence: 99%